Mining-induced displacement and resettlement: an analytical review - Mandishekwa, Robson; Mutenheri, Enard (African Journals Online, 2021)
Generally, mining-induced displacement has been less considered in research on development-induced displacement. Specifically, economists have relegated displacement studies to other disciplines despite displacement’s economic relevance. This paper seeks to outline development-induced displacements and their linkages with economic activities and life satisfaction among the displaced in post-displacement location. To attain this, an integrated literature review was done. Findings indicate scarcity of literature on economic consequences of mining-induced displacement and its linkage with economic activities and life satisfaction. A theoretical proposition for these linkages is made. The study also reveals that mining-induced displacement is equally important in displacement studies. The study recommends that economists must put more effort in mining-induced resettlement studies given that it has the potential to resettle more people.